Leaf anatomy of Celtis iguanaea (Cannabaceae): a contribution to the classification and taxonomy of the species - Henrique Borges Zamengo; Dion Adry de Souza Ferreira; Flávia Maria Leme; Rosani do Carmo de Oliveira Arruda (Rodriguésia)
Abstract Over the last two decades, the circumscription of Celtis iguanaea has been questioned due to the difference between the current characterization and others drawn up from specimens native to Curaçao, the type locality. This problem affects the species richness of the genus, as different species are mistakenly identified as C. iguanaea. Besides taxonomic challenges, this misinterpretation harms other anatomy, morphology, ontogeny and other study fields. To mitigate this problem, this article presents the first morpho-anatomical description of the leaves of C. iguanaea, based on specimens native to Curaçao. Herborized leaves were processed for analysis using light microscopy and scanning electron microscopy. The study identified the presence of multicellular and unicellular trichomes - the first secretory and the last non-secretory, anomocytic-type stomata, large cystoliths of silica on both leaf surfaces with apex projected beyond the epidermal surface, and dorsiventral mesophyll. Mucilaginous cells were widely distributed in the epidermis and in the cortical region of the midrib and petiole. The vascular system had collateral-type bundles. The petiole had a concave-convex shape and a single arch-shaped vascular bundle. These results can help to elucidate taxonomic problems related to C. iguanaea delimitation, and its congeners.